PERSPEKTIF LIVING VALUES EDUCATION (LVE) DALAM KAJIAN FILSAFAT PENDIDIKAN INDONESIA BERBASIS 3N (NALAR, NURANI, DAN NALURI) - I Putu Suardipa (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
Values provided by Living Values Education (LVE) is the value of the process of charactereducation that is done with various methods and approaches so as to create qualified humanresources based on academic and religious the best solution in instilling values through educatorsand learners in cooperation in achieving the educational goals of Indonesia. LVE in the contextof education focuses on humanized learning through 3N (Nalar, Nuranar, and Naluri) which isstrong and characteristic. The context of reasoning is that humans can determine moral, ethicaland aesthetic values. Conscience is the application of moral consciousness that grows anddevelops in the human heart in concrete situations. Instinct or instinct is a pattern of behaviorand reaction to a certain stimulus. Instinct in the context of learning more focused on the abilityof teachers to make teachers have a motherly instinct or fatherly instinct. In this role, the teachermust make the learning process of "humanization" (humanizing human) learning based on love,teasing and foster forming the atmosphere of principled in kinship, kindness, empathy, love andappreciation toward others. Through this learning education will greatly help students / learnersto personality independent, healthy physical, healthy mental, smart, and become an ideal memberof society.